A female patient with recurrent lung lesion and hilar lymphadenopathy - Zhan, Yangqing; Cheng, Linling; Cox, Gerard; Kolb, Martin; Chen, Ruchong; Chen, Rongchang; Zhong, Nanshan (Journal of Thoracic Disease, 2017)
Joint hospital grand rounds have been held in Guangzhou Institute of Respiratory Disease (GIRD) routinely every week for more than 10 years. Recently, more and more hospitals are taking part in our joint rounds through real-time video communication. Such events are broadcast live to healthcare providers from up to 500 hospitals in China.